Motivational Dimensions In Alfred Schutz’s Phenomenology: Understanding Secondhand Consumption Lifestyle Among Universitas Negeri Makassar Students - Muh Ichwan Musa; Muh Al Fatah Arief Putra; Tuti Adi Tama (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study explores the phenomenon of secondhand consumption among students at Universitas Negeri Makassar (UNM) through Alfred Schutz’s phenomenological framework. The research aims to uncover the motivational dimensions that shape students’ engagement with secondhand goods as part of their urban lifestyle. Using a qualitative approach and phenomenological design, the study focuses on understanding the subjective meanings behind students’ thrifting behavior. Data were collected through in-depth interviews, participant observation, and social media documentation at several major secondhand markets and thrift shops in Makassar. The analysis, following Schutz’s typifications of “because of motive” and “in order to motive”, revealed four central themes: economic efficiency, self-identity expression, environmental awareness, and the influence of digital communities. Findings indicate that thrifting among UNM students is not merely a cost-saving strategy but a reflective social practice that integrates aesthetic creativity, moral consciousness, and sustainability values. Moreover, social media serves as a cultural catalyst that transforms secondhand consumption into a medium for identity construction and digital participation. The study concludes that thrifting functions as a multidimensional cultural strategy through which students negotiate modernity, sustainability, and self-expression within the dynamic urban culture of Makassar.